Development of water trash collector - P. N. F. M., Shamsuddin; Muhamad Arifpin, Mansor; M. S. A., Hadi; N. Z., Abidin; R., Ibrahim (Scientific Academia, 2020)
Domestic waste disposal into rivers or lakes leads to drop-in water quality and ultimately will have a more vital impact on water pollution. Several countries built a semi and fully automation craft that equipped with the new system and came along with the technology development to facilitate the garbage collection task. The development of automation vehicle is meaningful for reducing the garbage as well as the manpower consumption for handling the cleanliness process. This project focuses on designing a high stability of Water Trash Collector (WTC) model and fabricate this vehicle with the high stainless-steel material. catamaran model is the suitable hull-type to collect a load of the garbage on the water surface. Besides, the objective for the electrical part is to develop the remotely WTC by using SkyFly controller and battery as the main power source. 3D Catamaran model is sketched in Siemen NX10 software based on USV element information gathered. Trash Bin collector and waterwheel are added in the design for collecting purposes and movement respectively. Square hollow mild stainless steel is a suitable material to create the frame for WTC because it is low cost, high corrosion resistant, sturdy and long-lasting materials. The power system in WTC is equipped with SmartDrive Duo-30, SmartDrive Duo-10, two high torque electric scooter motor, DC gear worm motor and FlySky Controller. WTC was performed well on the lake without any leakage on the both hull after attached the shafts and propellers. WTC is operated and moved as the motors are being driven by the controller. For future work, an embedded system of WTC needs to be autonomous for collecting the garbage.